Motives of large multinationals investing in small transition countries: A literature review - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
Economic theory suggests that multinationals have clear objectives when investing abroad. It lists a considerable number of factors which may influence the decision but it falls short of explaining them. The paper investigates how the most popular hypotheses presented in the literature perform in the light of recent experiences. It reviews a series of case studies on western multinationals which entered into a joint venture with eastern companies. It comes to the conclusion that investment decisions are governed by a bundle of overlapping motives. The benefits of geographically dispersed but well co-ordinated activities are seen in certain types of spill-overs that can only be generated in networks. These benefits can be best described as economies of scope.
Keywords: 330; Internationale Unternehmenskooperation; Direktinvestition; Multinationales Unternehmen; Westliche Staaten; Osteuropa